Application of Ecucandy in Listening Skills Learning of Descriptive Texts for Grade IX Students of SMP Negeri 1 Telaga - Tedi Korompot; Muslimin; Eka Sartika (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aimed to describe the implementation of Educandy in teaching listening skills for descriptive texts to ninth-grade students at SMP Negeri 1 Telaga and to identify students’ responses toward the use of the media. This study employed a descriptive approach with a qualitative research design. The population consisted of all ninth-grade students of SMP Negeri 1 Telaga, while the sample included 28 students and one Indonesian language teacher. Data were collected through observation, interviews, documentation, and learning achievement tests. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques to obtain a clear description of the learning process and outcomes. The findings revealed that the implementation of Educandy in descriptive text learning effectively improved students’ listening comprehension skills. This was indicated by the results of the Educandy quiz, which showed that 25 students achieved learning mastery with scores ranging from 120 to 193, while 3 students were still categorized as low achievers. The percentage of students’ learning mastery reached 89.29%. In addition, students gave positive responses to the use of Educandy because the media made the learning process more interesting, interactive, enjoyable, and capable of increasing students’ learning motivation and understanding of descriptive text materials.